Evaluation of Smart Grid Implementations in the Consumer's Energy Bill - Boldt, Diogo (2021)
The need to increase the share of renewable energy resources in several countries around the world led to the development of new strategies, in order to implement more effective energy policies. These resources have a distributed nature and are one of the main paths to incentive the reduction of CO2 emissions, and their impact on the environment. Many countries are making efforts to advance in the implementation of their own strategies to achieve the fossil fuels independency. Therefore, the intent is to stipulate energy policies that increase renewable energy share in the energy mix. These policies depend on regulations, taxation, incentives and promotional schemes. In this paper, it is presented a brief introduction to the energy policies in two countries, Denmark and Finland. Demand Response (DR) aspects and its impact in the energy market are also discussed.